Enablers and barriers for hearing parents with deaf children: Experiences of parents and workers in Wales, UK - Julia Terry (Wiley, 2023)
Abstract Background More than 90% of deaf children are born to hearing families who know little about deafness. Benefits from hearing screening at birth are often lost, as families find little information about pathways for deaf children but are key to ensuring deaf children receive relevant language and communication support. Systems surrounding deaf children and family members are crucial for children's health and social development. Experiences of hearing parents raising deaf children and understanding factors that influence families' experience of navigating pathways for deaf children through health and education services are currently underreported. Methods An exploratory study was conducted in Wales, UK. Twenty participants were interviewed, including 10 hearing parents of deaf children and 10 people who work with deaf children using semistructured interviews. Bronfenbrenner's ecological systems theory was used as a lens to explore the micro‐, meso‐, exo‐, macro‐ and chronosystems that surround children and families. This study explores potential supports and barriers in those systems. Findings Findings are reported under two broad headings: enablers and barriers. Under enablers, it was found that provision of resources, supporting people and knowledge were key factors. Under barriers, a lack of knowledge, lack of provision and battling services and attitudes were key issues that need addressing. Conclusion Hearing parents of deaf children in Wales, UK reported experiencing a range of enablers and barriers that impact upon their experiences of raising a deaf child. Further provision is needed by policymakers and governments to recognise support needs to improve the outcomes for deaf children. Patient or Public Contribution This project was developed from initial discussions with the stakeholder reference group and progressed with the group's deaf panel and hearing parents with deaf children. The project's steering group was involved in study design, recruitment and continuous feedback on all stages of the research process.